Worship and theology in England : bk 2 (vols III & IV) - DAVIES, Horton (Grand Rapids, MI Eerdmans, 1961)
Contents : bk 2 [vol III] From Watts and Wesley to Mauirice, 1690-1850; [vol IV] From Newman to Martineau, 1850-1900.
Includes bibliographical references and index.
Keywords: Public worship -- history; Church history -- modern period, 1485- -- England; Theology, doctrinal -- History -- England